Factors Influencing Household Recycling Behavior in Lima, Peru: Insights for Social Marketing Strategies - Tassano Ramos, Alvaro Santiago (2024)
The main objective of this study is to find out what factors impact household recycling behavior with the aim to guide the development of a social marketing strategy to promote this behavior. The study was based on a structural equation model using the three factors that make up the Theory of Planned Behavior (TPB). In addition, four more variables were analyzed: environmental awareness, moral standards, situational factors, and recycling service and infrastructure. The results of 254 valid questionnaires reveal that the subjective norm–or social pressure–was the only variable of the TPB to affect recycle intention significantly. Considering the role social pressure has on recycling behavior, it is necessary to implement a social marketing strategy that maximizes the visibility of this activity and include the participation of the community as much as possible.